Strategi Transfer Pengetahuan pada Community Health Workers dalam Pelayanan Kesehatan Primer: Literature Review - Fitri Ika Arde Yani; Setya Haksama (Universitas Pahlawan Tuanku Tambusai, 2026)
Community Health Workers (CHWs) play a crucial role in primary health care by serving as a bridge between health systems and communities. The expanding and increasingly complex role of CHWs requires sustainable capacity-building mechanisms, one of which is knowledge transfer. This literature review aims to identify and synthesize knowledge transfer strategies implemented among Community Health Workers in primary health care settings and to explore their contributions to strengthening CHW capacity. A literature search was conducted in the Scopus database using keywords related to knowledge transfer and Community Health Workers. Articles were selected based on predetermined inclusion and exclusion criteria, resulting in five eligible studies for review. The findings revealed that knowledge transfer strategies among CHWs can be categorized into three main approaches: training-based knowledge transfer, technology-assisted knowledge transfer, and collaborative knowledge transfer. These strategies contributed to improvements in knowledge, skills, case detection capacity, and the quality of health services delivered by CHWs. However, their implementation continues to face several challenges, including limited technological infrastructure, low digital literacy, resource constraints, and socio-cultural factors. This literature review concludes that knowledge transfer is an essential strategy for strengthening the capacity of Community Health Workers and should be developed in accordance with local needs and contexts to support effective and sustainable primary health care.